Environmental Design of Indonesian Cultural Background on Creative Design Incubation of 'Legacy of Moksha' - Kukuh, Edward; Yanuar, Naldo (ULTIMART Jurnal Komunikasi Visual, 2023)
Indonesia has an almost countless number of cultures, making it one of the countries with thousands of cultures and their diversity. Seeing this fact, it is quite unfortunate that Indonesian people at this time do not respect their own culture, and far prefer culture from abroad. This is due to the existence of globalization which makes it easier for information to enter rapidly, especially in the field of creative media and entertainment which is one of the negative effects for Indonesian culture, namely local culture which is shifted by foreign culture. It is hoped that this project will be able to compete with this problem by creating a creative concept based on Indonesian culture, to introduce and re-creating love for Indonesian culture, through a more interesting and creative video game concept. Therefore, a plan to create a creative concept that will be the base for creating a creative media, that is expected to attract Indonesian people's interest in their own culture. Some methods such as literature study, documentation study, and surveys are used, which are based on several sources such as literature books, articles, journals, and the results of past research that has been done before. The data obtained will be a guide for making a concept book, which will be the final result of designing the Legacy of Moksha game concept. Keywords: indonesian; culture; intellectual product property; concept art; environment; design